Implementation of Community-Scale Bio-Solar Hybrid Renewable Energy Systems with Energy Storage to Enhance Microgrid Stability and Local Sustainability - Budi Artono; Jusra Tampubolon (International Forum of Researchers and Lecturers, 2024)
The increasing demand for sustainable and reliable energy solutions in remote and off-grid communities has led to the exploration of hybrid bio-solar renewable energy systems. This paper examines the implementation of a hybrid bio-solar system with energy storage to improve microgrid stability and support local sustainability. By combining biomass and solar power with energy storage, the system provides a reliable, clean, and cost-effective energy supply, addressing intermittency and enhancing grid resilience. The research covers system design, power flow simulation, voltage and frequency stability, and both economic and environmental analyses to assess system effectiveness. The results show that the hybrid bio-solar system significantly improves energy reliability, reduces carbon emissions, and offers a more stable energy supply compared to diesel or grid-based systems. The system's scale and configuration are crucial in optimizing cost-effectiveness, with larger systems yielding better long-term benefits. Local community involvement is key to managing and maintaining the system, ensuring its sustainability. Compared to other renewable energy hybrids like wind-solar or solar-diesel, the bio-solar system offers superior reliability and cost-efficiency, especially where biomass is abundant. The paper concludes with recommendations for scaling these systems and emphasizes the importance of supportive policies for accelerating sustainable energy transitions.